Dengue viremia kinetics in asymptomatic and symptomatic infection. (December 2020) - Matangkasombut, Ponpan; Manopwisedjaroen, Kajohnpong; Pitabut, Nada; Thaloengsok, Sasikanya; Suraamornkul, Swangjit; Yingtaweesak, Tawatchai; Duong, Veasna; Sakuntabhai, Anavaj; Paul, Richard; Singhasivanon, Pratap
Highlights: Lower dengue viremia in asymptomatic than in symptomatic febrile dengue patients. Slow decay in dengue viremia in asymptomatic dengue infection. Transmission control improvement to cover long-lived asymptomatic dengue is needed. Abstract: Background: Dengue infection is a global health threat. While symptomatic cases contribute to morbidity and mortality, the majority of infected people are asymptomatic but serve as an important reservoir. However, the kinetics of viremia in asymptomatic infections remains unknown. Methods: We enrolled 279 hospital-based symptomatic index cases and quantified dengue virus (DENV) RNA at enrollment and at the day of defervescence. To identify asymptomatic cases, 175 household members of index cases were monitored for clinical symptoms during follow-up, and blood was taken twice weekly to test for and quantify DENV RNA until cleared. Results: We detected DENV in thirteen asymptomatic household members (7.43%). Their DENV serotypes were primarily the same as those of their family index cases. The median peak DENV viremia in asymptomatic subjects was lower than that of symptomatic individuals during the febrile phase, and the viral decay rate was slower in asymptomatic infections. Conclusions: DENV level and kinetics in asymptomatic individuals differed significantly from those of symptomatic cases. Despite the lower viremia, the slower decay rate in asymptomatic infections could lead to their prolonging the infectious reservoir. The improvement of transmission control to prevent such long-lived asymptomatic infections from transmitting the DENV is needed.